2005
DOI: 10.1111/j.1460-9568.2005.04003.x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal ontogeny of hippocampal expression of the mineralocorticoid and glucocorticoid receptors in the common marmoset monkey

Abstract: The mineralocorticoid receptor (MR) and glucocorticoid receptor (GR) are nuclear transcription factors that mediate many of the basal and stress functions and effects of the corticosteroid hormones, including those related to brain development. Despite this, relatively little is known about the postnatal ontogeny of MR and GR gene and protein expression in the central nervous system, and this is particularly true of the primates, including humans. Here we describe the postnatal ontogeny of central MR and GR ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…This association is consistent with previous reports of relationships between increased HPA axis activity and age-related hippocampal volume loss (5). There have been conflicting reports about the density of GC receptor expression in the hippocampus relative to other regions of the primate brain (41,42,43). Nonetheless, our findings raise the intriguing possibility that increased GC levels may have a disproportionate impact on the AD disease process as it develops in the hippocampus and other structures of the medial temporal lobe (e.g., entorhinal cortex) (44).…”
Section: Discussionsupporting
confidence: 82%
“…This association is consistent with previous reports of relationships between increased HPA axis activity and age-related hippocampal volume loss (5). There have been conflicting reports about the density of GC receptor expression in the hippocampus relative to other regions of the primate brain (41,42,43). Nonetheless, our findings raise the intriguing possibility that increased GC levels may have a disproportionate impact on the AD disease process as it develops in the hippocampus and other structures of the medial temporal lobe (e.g., entorhinal cortex) (44).…”
Section: Discussionsupporting
confidence: 82%
“…The ontogeny of the GR has been studied in rodent and recently also in marmoset monkey brain tissue (Van Eekelen et al, 1991;Schmidt et al, 2003;Pryce et al, 2005). Previous studies on rat hippocampus showed that prenatal stress reduced neurogenesis and caused an impairment of hippocampal-dependent spatial learning as observed later in life (Lemaire et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of the genotypes was done with postmortem tail biopsies as described (Oddo et al, 2003). Groups 5/6: The housing conditions for rats and common marmoset monkeys were as described (Nyffeler et al, 2007;Pryce et al, 2005).…”
Section: Group4mentioning
confidence: 99%
“…Louis, MO) staining for 5 -10 min as described Nyffeler et al, 2007;Pryce et al, 2005). Counterstaining of Reelin-IP labeling was done with 0.25% Cresyl violet according to standard protocols.…”
Section: Group4mentioning
confidence: 99%